POLITICAL JUSTICE IN THE DIGITAL ERA: A PERSPECTIVE OF MILLENNIAL EDUCATIONAL PERSONNEL AND LECTURERS - Ryanda Iqbaal Pradipta Widadi; Mardian Idris Harahap (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2026)
This study examines political justice in the digital era from the perspective of millennial academic staff and lecturers, with a specific focus on the educator community at the Faculty of Ushuluddin and Islamic Studies and the Faculty of Sharia and Law, Universitas Islam Negeri Sumatera Utara (UINSU). Millennials, defined as individuals born between 1981 and 1996, occupy a strategic position as a generation that bridges classical religious traditions, academic discourse, and contemporary digital information flows. In the context of Islamic higher education, their understanding of political justice is shaped not only by normative religious values and legal-political knowledge, but also by exposure to digital media, online political narratives, social media discussions, and public debates on justice, democracy, and governance. This study uses a quantitative approach with purposive sampling involving 12 respondents. Data were collected through a 15-item Likert scale questionnaire covering four dimensions: digital information exposure, political awareness, perception of justice, and understanding of political justice. The findings show that digital information exposure, as the independent variable, obtained a mean score of 3.21, while political justice understanding, as the dependent variable, obtained a higher mean score of 3.96. The correlation analysis indicates a strong positive relationship between digital information exposure and political justice understanding, with a correlation coefficient of r = 0.86.